Penggunaan Media Flashcard untuk Meningkatkan Keterampilan Menulis Teks Prosedur Peserta Didik Kelas IV di SDN Sumber V Surakarta - Vita Sulistya; Puji Rahayu; Trima Pangestuningsi; Mei Iriana (Universitas Sebelas Maret, 2025)
This study was motivated by the low writing skills of students, particularly in the Indonesian language subject, specifically on procedural text material. Students struggle to develop ideas into well-structured sentences. This issue arises because fourth-grade teachers at SDN Sumber 5 predominantly use traditional teaching methods and rely heavily on textbooks, resulting in suboptimal student writing performance. Therefore, this study aims to improve students' procedural text writing skills through the use of flashcard-based learning media. The research employs a Classroom Action Research (CAR) approach, involving 13 students as subjects. The results showed a significant improvement in writing skills. In the pre-cycle stage, only 15% of students met the minimum competency standards (KKTP). This figure increased to 85% in the first cycle and further rose to 92% in the second cycle. These findings indicate that the use of flashcards is effective in enhancing students’ ability to write procedural texts.